2013
DOI: 10.2527/jas.2013-6407
|View full text |Cite
|
Sign up to set email alerts
|

Mice do not accumulate muscle lipid in response to dietary conjugated linoleic acid1

Abstract: Dietary CLA decreases body fat in several species and in pigs this is accompanied by increased muscle lipid. Our objective was to determine if mice could be used as a model for CLA-induced increased marbling in pigs. We used our model of enhanced CLA response, where mice fed coconut oil (CO) lose more body fat than mice fed soy oil (SO). Mice (21 d old; Imprinting Control Region [ICR]) were fed SO or CO diets for 6 wk followed by 12 d of 0 or 0.5% mixed isomer CLA. Ether extraction determined that thigh muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Therefore we measured serum ketone bodies as an indication of fatty acid oxidation, but did not find any differences between dietary groups. We previously have showed that CPT activity was decreased by CLA in the CO-fed mice [25]. Hence it appears that lipid oxidation is not being enhanced in the CO ?…”
Section: Discussionmentioning
confidence: 90%
“…Therefore we measured serum ketone bodies as an indication of fatty acid oxidation, but did not find any differences between dietary groups. We previously have showed that CPT activity was decreased by CLA in the CO-fed mice [25]. Hence it appears that lipid oxidation is not being enhanced in the CO ?…”
Section: Discussionmentioning
confidence: 90%